2009
DOI: 10.1111/j.1439-0523.2008.01543.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and isolation of a new x‐type HMW glutenin subunit 1Dx1.6t gene from Aegilops tauschii

Abstract: A new x-type HMW glutenin subunit, designated as 1Dx1.6 t from Aegilops tauschii was identified and characterized by SDS-PAGE and MALDI-TOF-MS. This subunit is located between 1Dx2 and 1Dx1.5 t and possesses a molecular mass (M r ) of 88565.8 Da. Its complete coding sequence was amplified via allele-specific PCR (AS-PCR), and the amplified product was cloned and sequenced. The authenticity of the cloned 1Dx1.6 t gene was confirmed by successful expression of its open reading frame in Escherichia coli. The mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…To date, only limited numbers of x‐type HMW glutenin genes have been isolated from Ae. tauschii accessions (Lu et al 2005; Wan et al 2005; Zhang et al 2008b; An et al 2009 ). In the current, two novel x‐type HMW glutenins 1Dx3 t and 1Dx4 t were cloneded and characterized from Ae.…”
mentioning
confidence: 99%
“…To date, only limited numbers of x‐type HMW glutenin genes have been isolated from Ae. tauschii accessions (Lu et al 2005; Wan et al 2005; Zhang et al 2008b; An et al 2009 ). In the current, two novel x‐type HMW glutenins 1Dx3 t and 1Dx4 t were cloneded and characterized from Ae.…”
mentioning
confidence: 99%
“…tauschii accessions found to be superior for various components of heat tolerance. Recent studies indicate good prospects for extending the range of traits that may be introgressed from Aegilops taushii (An et al. 2009, Takumi et al.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, the substitution from cysteine to arginine in the y-type subunit could be responsible for the lower dough quality by decreasing the number and affecting the pattern of disulphide cross-links in the gluten in polymers, which have been verified by site-directed mutagenesis technology. Previous studies have suggested that the number and distribution of cysteine residues were two of the key factors influencing wheat dough quality [18,34,48,49]. Although exploiting the new HMW-GSs genes from wild species was an effective way to broaden the genetic diversity of wheat [8,21,31,35,50,51], the gene engineering could be utilized to improve the dough quality by modifying the number or the structure of cysteine residues in HMW subunits [11,35].…”
Section: Discussionmentioning
confidence: 99%
“…Several favorable genes for the storage protein have been identified in Ae. tauschii [18][19][20][21][22][23][24]. However, few of them were introgressed into wheat and applied in wheat breeding.…”
Section: Introductionmentioning
confidence: 99%